Pengaruh Social Media Marketing, Kesadaran Merek, Dan Kepercayaan Merek Terhadap Niat Beli - Sari, Septi Kartika; Hayuningtias, Kristina Anindita (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Social media is very important in the purchasing intention activities of someone ho will buy a product online which they do with brand awareness and brand trust.This type of research was carried out using descriptive quantitative processing using SmartPLS 3.3.4 software. Purposive sampling technic was used in this research. Data collection was taken from 124 questionnaires via googlefrom. The result of this research sho that social media marketinh has a positive and significant effect on brand awareness and brand trust. Brand awareness and brand trust have a positive and significant on purchase intention.